Impact of Vaginal Estrogen on the Urobiome in Postmenopausal Women With Recurrent Urinary Tract Infection. Issue 1 (January 2022) - Jung, Carrie E.; Estaki, Mehrbod; Chopyk, Jessica; Taylor, Bryn C.; Gonzalez, Antonio; McDonald, Daniel; Shin, Jenny; Ferrante, Kimberly; Wasenda, Erika; Lippmann, Quinn; Knight, Rob; Pride, David; et al.
Abstract : Objective: The aim of this study was to describe effects of vaginal estrogen (VE) on the urogenital microbiome in postmenopausal women with recurrent urinary tract infections (rUTIs). Methods: This is a secondary analysis of 17 participants enrolled in a randomized controlled trial of VE versus placebo on urinary tract infection recurrence in postmenopausal women with rUTIs. Paired clean-catch urine samples were collected at baseline and after 6 months of VE and sequenced using 16S rRNA gene sequencing. Sequence reads were analyzed using Quantitative Insights Into Microbial Ecology 2. Changes in α diversity, β diversity, and differentially abundant genera were measured between paired baseline and 6-month samples and between those with a urinary tract infection at 6 months ( failures ) and those without ( successes ). Results: Of the 17 women, 11 were successes and 6 were failures after 6 months of VE treatment. There was a significant change in α diversity from baseline to month 6 in samples overall (Kruskal-Wallis χ 2 = 3.47, P = 0.037) and in the treatment success group (Yuen T = −2.53, P = 0.035). The increase in relative abundance of Lactobacillus crispatus, Lactobacillus gasseri, and Lactobacillus iners AB-1 was correlated with month 6. A relative bloom of L. crispatus compared with L. gasseri was associated with treatment success (Kruskal-Wallis χ 2 = 4.9, P = 0.0014). Conclusions: Lactobacillus increases in the urogenital microbiome of postmenopausal women with rUTI after 6 months of VE. However, only the relative increase in L. crispatus specifically may be associated with treatment success. Abstract : Supplemental digital content is available in the text.